Comparison of the effectiveness of three extractants in extracting potassium, calcium and magnesium from tropical peat soils - Abdul Reeza, Ameera; Hussin, Aminuddin; Ahmed, Osumanu Haruna (Finnish Peatland Society, 2021)
Peat soils are frequently analysed using the same standard methods and extractants as for mineral soils, despite the distinctive nature of organic soils. The extractants used are well-suited for peat soils of near-neutral pH but it is still unclear whether they are suitable for acidic tropical peat soils. The study reported here compared the effectiveness of three standard reagents in extracting potassium, calcium, and magnesium from tropical peat of different degrees of decomposition, collected from three field locations in peninsular Malaysia. Three basic cations (K+ , Ca2+ and Mg2+) were extracted using Mehlich 1, NH4OAc (ammonium acetate) buffered at pH 7 and NH4OAc at pH 4. The results showed that raising the pH of the extractant reduced the amounts of K+, Ca2+ and Mg2+ extracted. The average amounts extracted by Mehlich 1 and NH4OAc at pH 4 were frequently significantly higher than the amounts extracted by NH4OAc at pH 7, in most of the peat types sampled regardless of location. Compared with the extraction using NH4OAc at pH 7, the extractions with Mehlich 1 and NH4OAc at pH 4 are likely to provide closer estimations of these basic cations, because the pH of the extractants reflects the true pH of tropical peat soils.